The rise of Korean leadership : emerging powers and liberal international order - Ikenberry, G. John; Mo, Jongryn; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
The book provides a portrait of the rise of Korea as a global leader of the last decade and its impact on international liberal order.
Keywords: Science; Science; Science, general